Formula Alternatives for Nutrition Therapy of Children with Cow's Milk Protein Allergy - Gennadiy A. Novik; Maria V. Zhdanova; Yulia O. Zaitseva; Anastasiia S. Demidova ("Paediatrician" Publishers LLC, 2021)
Well-recognized tactic for the management of formula-fed children with cow's milk protein allergy (CMPA) is exclusion of whole cow milk protein and its replacement with extensively hydrolyzed or amino acid formula. One of the most topical issue is the choice of therapeutic formula for a child with CMPA. This article presents information about the clinical manifestations of CMPA and describes the principles of nutrition therapy. All the stages of preparation of adapted therapeutic formula are discussed in detail. It has been shown that the choice of therapeutic formula for a child with CMPA depends on the disease clinical manifestations, their severity, and the presence of comorbid conditions. Current requirements for extensively hydrolyzed formula are reduced to limitations in the size of peptides with immunoreactive properties and indicate the need for evidence of the clinical efficacy of such formula in double-blind placebo-controlled studies.